2014
DOI: 10.1007/s00779-014-0766-3
|View full text |Cite
|
Sign up to set email alerts
|

Performative technologies for heritage site regeneration

Abstract: Heritage sites are an important part of understanding our role in history. They have the potential to teach us important lessons, such as where we came from and subsequently, the people it has made us today. As members of a large, heritage-led, regeneration project, we are working with the Hafod-Morfa Copperworks, a heritage site in the Lower Swansea Valley where there is not much to see or hear. The few ruins at the site make it difficult to imagine what the site would have been like back in its heyday. Our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Ideas for improvements of guided tour: The children proposed, e.g. (1) a treasure hunt activity with hints to provide a playful experience during the guided tour, (2) to explain the guided tour through pictures, (3) an activity where children could dig up the destroyed children's room and discover what was hidden under the stones, (4) to perform a drill of the bomb alarm and experience the rushing of people into the shelter. Thus, Children's proposals revealed a need for participative and hand-on activities during the guided tour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideas for improvements of guided tour: The children proposed, e.g. (1) a treasure hunt activity with hints to provide a playful experience during the guided tour, (2) to explain the guided tour through pictures, (3) an activity where children could dig up the destroyed children's room and discover what was hidden under the stones, (4) to perform a drill of the bomb alarm and experience the rushing of people into the shelter. Thus, Children's proposals revealed a need for participative and hand-on activities during the guided tour.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural heritage sites play a crucial role in how people understand history and culture. According to Betsworth et al [2] they have "the potential to teach us important lessons, such as where we came from and subsequently, the people it has made us today". Interactive experiences for these contexts are commonly used to complement learning concepts rather than being considered as independent learning tools [5,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following previous scholarship on place-based digital cultural heritage, we both understand heritage encounters to be embodied, and consituted of 'personal, social, cultural, and physical experienial qualiies' [8]. Paricularly, Ciolfi [8] and Fosh et al [23] emphasise the role of embodiment in experiencing a variety of cultural and natural heritage sites, while Betsworth et al [24] pay atenion to the role of spectators and bystanders in performaive digital heritage applicaions in a disused Copperworks site. In the later study, interviews and observaions showed not only that paricipant experiences were diverse, but that they were highly coningent on how paricipants responded to the tangible and emoional resources, as well as the acivity on the sites, which were not strictly scripted on the mobile applicaion.…”
Section: Adequately Accouning For Transmedial Digital Cultural Heritamentioning
confidence: 99%
“…There are few studies that combine the use of projection devices and fiducial markers to created located information presentation. One such system is presented in [1] where the authors describe a study that took place at the National Botanic Garden of Wales. The study explored the participants' reactions to a prototype that utilised a pico-projector attached to an iPod.…”
Section: Using Markers For Mobile Information Deliverymentioning
confidence: 99%